On the sizes and distances of the sun and moon. - Aristarchus, of Samos, author. Link
1 online resource
Keywords: This book offers the Greek text and an English translation of Aristarchus of Samos's On the Sizes and Distances of the Sun and Moon, accompanied by a full introduction, detailed commentary, and relevant scholia. Aristarchus of Samos was active in the third century BC. He was one of the first Greek astronomers to apply geometry to the solution of astronomical problems as we can see in his only extant text, On the Sizes and Distances of the Sun and Moon. Alongside the Greek text and new English translation, the book offers readers the Latin text and English translation of Commandino's notes on the text. Readers will also benefit from a comprehensive introductory study explaining the value of Aristarchus's calculations and methodology throughout history, as well as detailed analyses of each part of the treatise. This volume will be of interest to students and scholars working on ancient science and astronomy and the general reader interested in the history of science.